Perancangan Aplikasi Pembayaran SPP pada SMA Swasta Etislandia Medan - Tobing, Putra Halomoan; Hutapea, Marlyna I.; Siringoringo, Rimbun (TAMIKA: Jurnal Tugas Akhir Manajemen Informatika & Komputerisasi Akuntansi, 2024)
Information and communication technology makes it possible to work in the school sector. Currently there is a data case in the school sector that handles education fee installments. To help achieve an ideal data framework for managing education fee installments, an information system that is useful, precise and fast is needed. Organizing carried out physically will hinder the organization's implementation as school cash manager. The creator conducted a search and created a Fee Installment Instruction Application using the Java programming dialect in the Android Studio application and Firebase as the database. The aim of this research is to find out what pictures and problems arise from the system that is already running and the system that will be designed, as well as speed up the regulatory portion in serving instruction fee installments and make progress on the old framework by replacing it with a modern framework.